2000
DOI: 10.2307/3454632
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology Studies on Occupational and Environmental Exposure to Mutagens and Carcinogens, 1997-1999

Abstract: Molecular epidemiology is a new and evolving area of research, combining laboratory measurement of internal dose, biologically effective dose, biologic effects, and influence of individual susceptibility with epidemiologic methodologies. Biomarkers evaluated were selected according to basic scheme: biomarkers of exposure-metabolites in urine, DNA adducts, protein adducts, and Comet assay parameters; biomarkers of effect-chromosomal aberrations, sister chromatid exchanges, micronuclei, mutations in the hypoxant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…As many of the compounds in diesel exhaust are bio-transformed to DNA-damaging agents, genetic differences in enzymes involved in the biotransformation have been found to influence the biomarker level [21]. Previous studies have shown inconsistent effects of genotypes on biomarkers of exposure to environmental pollutants and the consequences of this exposure [20,22,23]. Chromosome aberrations were increased in bus drivers with the null genotype of GSTM1 [17] and a higher DNA-adduct level was found in mothers with the GSTM1-null genotype, exposed to varying amounts of environmental pollution in the Czech Republic [24].…”
Section: Introductionmentioning
confidence: 99%
“…As many of the compounds in diesel exhaust are bio-transformed to DNA-damaging agents, genetic differences in enzymes involved in the biotransformation have been found to influence the biomarker level [21]. Previous studies have shown inconsistent effects of genotypes on biomarkers of exposure to environmental pollutants and the consequences of this exposure [20,22,23]. Chromosome aberrations were increased in bus drivers with the null genotype of GSTM1 [17] and a higher DNA-adduct level was found in mothers with the GSTM1-null genotype, exposed to varying amounts of environmental pollution in the Czech Republic [24].…”
Section: Introductionmentioning
confidence: 99%
“…Generations of epidemiologists, physicians, and scientists have used biomarkers to study a variety of conditions. Especially, biomarkers of internal dose and early biological effects as a biomarker of oxidative stress have been used in epidemiological studies [1]. Although a number of cohort studies have collected and preserved various biospecimens for use in molecular and genetic epidemiological studies [2,3], it is surprising that there has been little documentation concerning the intra-person variance and inter-person variance reliability associated with biomarkers [4].…”
Section: Introductionmentioning
confidence: 99%
“…The composition of automobile exhaust is complex and generally contains carbon monoxide, nitrogen oxides, particulates and polycyclic aromatic hydrocarbons (PAHs), nitroaromatics, benzene, 1,3-butadiene, sulfur dioxide and lead (4). Different biomarkers have been used to assess exposure to genotoxic compounds in general and occupational environment, ranging from the presence of mutagenic activity in urine to the induction of chromosomal damage in target and surrogate tissues (5).The hazardous traffic fumes contain a vari¬ety of pollutants which can cause respiratory problems and other systemic diseases including cancer (6). Traffic policemen exposed to vehicular emissions, work in noisy and polluted environment.…”
mentioning
confidence: 99%